Інституціалізація правоохоронної функції держави як напрям підвищення відповідальності держави перед людиною та суспільством в умовах сучасної України - Бакумов, О. С.; Bakumov, O. S. (Науковий вісник публічного та приватного права. - 2019. - Вип. 5, т. 1. - С. 27-34, 2019)
У статті показано взаємозв’язок між інституціалізацією правоохоронної функції держави та дією норм інституту юридичної відповідальності держави. Встановлено, що розгляд правоохоронної функції держави та правоохоронних органів тісно пов’язаний із переосмисленням ролі та значення інституту юридичної відповідальності держави. З’ясовано, що правоохоронна функція держави екзистенційно пов’язана із захистом прав і свобод людини і громадянина, а отже – із інститутом юридичної відповідальності держави. Окреслені основні напрями вдосконалення системи правоохоронних органів України на сучасному етапі проведення конституційної реформи.

The relationship between the institutionalization of the state law enforcement function and the action of the norms of the state legal responsibility institution was shown in the article. It was proved that the consideration of the law enforcement function of the state and law enforcement agencies is closely related to the re-thinking of the role and significance of the legal liability institution of the state. It was determined that the law enforcement function of the state is existentially connected with the protection of the human and civil rights and freedoms, and, consequently, with the legal liability institution of the state. The main directions of improving of the law enforcement system of Ukraine at the present stage of constitutional reform are emphasized in the manuscript. The importance of ensuring the effectiveness of the institute of legal responsibility of the state of public (civil) control over law enforcement bodies of the state by the institutions of civil society is emphasized. The necessity of compensation for the damage caused to an individual is characterized by the need to be repeatedly emphasized by the higher judicial bodies, which formulated guidance on the most complex and important issues that arise in the consideration and resolution of cases. It is concluded that the subject of implementation of the law enforcement function of the state is the system of law enforcement agencies of the state, which in Ukraine is only partially defined at the constitutional and legislative levels. Possibilities of applying the negative and positive legal responsibility of the state in the activities of law enforcement agencies are the more significant, the more important is the degree of independence of the law enforcement agencies, the more regulated at the level of special laws their organization and activity are and the more the general orientation of the activity of each body will be more pronounced. human-centric nature. Obviously, with the increase of the level of legal responsibility of the state is connected with the constitutionalization of the law enforcement function of the state, the gradual expansion of guarantees of the proper implementation by the law enforcement bodies of their activity. At the same time, the legislative basis of their activity must be aligned with the requirements of the Basic Law of Ukraine, and also consistent with the principles of legal responsibility of the state as a whole.

В статье показана взаимосвязь между институциализацией правоохранительной функции государства и действием норм института юридической ответственности. Установлено, что рассмотрение правоохранительной функции государства и правоохранительных органов тесно связан с переосмыслением роли и значения института юридической ответственности. Выяснено, что правоохранительная функция государства экзистенциально связана с защитой прав и свобод человека и гражданина, а значит – с институтом юридической ответственности. Обозначены основные направления усовершенствования системы правоохранительных органов Украины на современном этапе проведения конституционной реформы.
Keywords: держава; правоохоронна функція; правоохоронні органи; юридична відповідальність держави; конституційна реформа; state; law enforcement function; law enforcement agencies; legal liability of the state; constitutional reform; государство; правоохранительная функция; правоохранительные органы; юридическая ответственность государства; конституционная реформа